The article defines the essence of the concept "student family". The main factors of youth readiness to create a family are highlighted. The specific problems faced by student families are characterized, the main psychological causes of conflicts in stude - Посвістак, О.; Єфіменко, В. (Київський національний університет імені Тараса Шевченка, 2019)
The article defines the essence of the concept "student family". The main factors of youth readiness to create a family are highlighted. The specific problems faced by student families are characterized, the main psychological causes of conflicts in student families are identified and ways to solve social and psychological problems of the family are analyzed. The benefits of student families are shown.

Визначено сутність поняття "студентська сім'я". Виділено основні чинники готовності молоді до створення сім'ї. Охарактеризовано специфічні проблеми, з якими стикаються студентські сім'ї, виокремлено основні психологічні причини конфліктів у студентських сім'ях та проаналізовані шляхи вирішення соціально-психологічних проблем сім'ї. Показано переваги студентських сімей.
ПРОБЛЕМИ ТА ПЕРЕВАГИ СУЧАСНОЇ СТУДЕНТСЬКОЇ СІМ'Ї
Keywords: family psychology; young family; student family; family conflict; психологія сім'ї; молода сім'я; студентська сім'я; сімейний конфлікт